Pandemi (Covid-19) Sürecinde Spor Eğitimi Alan Öğrencilerin Senkron Uzaktan Eğitime Yönelik Görüşleri - Yılmaz, Metin; Savucu, Yüksel; Baş, Muhammet; Alpay, Numan (İbrahim ERDEMİR, 2022)
Amaç: Araştırmamızda; spor eğitimi alan öğrencilerin senkron uzaktan eğitim uygulamalarına yönelik görüşlerinin ortaya konulması amaçlanmıştır.Materyal ve Metot: Çalışmanın örneklemini 2020-2021 eğitim-öğretim yılı güz döneminde Fırat Üniversitesi Spor Bilimleri Fakültesinde öğrenim görmekte olan 225 öğrenci oluşturmaktadır. Uzaktan eğitime ilişkin görüşlerin değerlendirilmesi için Yıldırım ve ark. (2014) tarafından geliştirilen, 18 soru ve dört alt boyuttan oluşan “Uzaktan Eğitime Yönelik Öğrenci Görüşleri” ölçeği kullanılmıştır. Ölçeğe ait cronbach alpha güvenirlik katsayısı 0.864 olarak hesaplanmıştır. Veriler google forms aracılığıyla öğrencilere ulaştırılan ölçek formuyla elde edilmiştir. Normal dağılım gösteren verilerin analizinde betimsel istatistikler, bağımsız örneklem t testi ve tek yönlü varyans analizi (Anova) testi kullanılmıştır. Bağımlı değişkenler arasındaki ilişki durumunu saptamak amacıyla “Pearson Korelasyon Analizi” gerçekleştirilmiştir.Bulgular: Örneklem grubunun cinsiyet değişkeninde “öğreticilik” alt boyutunda kadın öğrencilerin lehine istatistiksel olarak anlamlı farklılıklar görülmüştür. Ayrıca öğrenim görülen bölüm ve sınıf düzeyi değişkenleri açısından anlamlı düzeyde farklılıklar bulunmuştur. Yapılan korelasyon analizi sonucunda ise ölçeğin “Kişisel Uygunluk” alt boyutu ile “Etkililik” alt boyutu (r=0.846; p<0.01) arasında pozitif yönde ve yüksek düzeyde ilişki olduğu görülmüştür.Sonuç: Sonuç olarak araştırmada yer alan spor bilimleri fakültesi öğrencileri senkron uzaktan eğitim uygulamalarını geleneksel eğitime nazaran yeterli düzeyde etkili bulmadıklarını ancak uzaktan eğitimin öğretici olduğunu belirtmişlerdir.

Aim: In this study, our aim is to reveal the views of students who receive sports education about synchronous distance education applications. Methods: The sample of the study consists of 225 students studying at the faculty of sports sciences in the fall semester of the 2020-2021 academic year. In order to evaluate the views on distance education, Yıldırım et al. (2014) and consisting of 18 questions and four sub-dimensions, the "Student Views on Distance Education" scale was used. The cronbach alpha reliability coefficient of the scale was calculated as 0.864. The research data were collected with the scale form delivered to the students via google forms. In the analysis of normally distributed data, descriptive statistics (frequency, arithmetic mean, standard deviation), independent sample t-test and one-way variance analysis (ANOVA) test were used. "Pearson Correlation Analysis" was conducted to determine the level of relationship among the dependent variables. Results: Statistically significant differences were observed in favor of female students in the sub-dimension of "instructiveness" in the gender variable of the sample group. In addition, significant differences were found among the variables of the department and grade level of the students. As a result of the correlation analysis, it was determined that there was a positive and highly significant relationship between the "Personal Suitability" sub-dimension and the "Effectiveness" sub-dimension (r=0.846;p<0.01). Conclusion: Consequently, the students of the faculty of sports sciences in the study stated that they did not find synchronous distance education practices effective enough compared to those of the traditional education, but that distance education was instructive.aim: In this study, our aim is to reveal the views of students who receive sports education about synchronous distance education applications.Methods: The sample of the study consists of 225 students studying at the faculty of sports sciences in the fall semester of the 2020-2021 academic year. In order to evaluate the views on distance education, Yıldırım et al. (2014) and consisting of 18 questions and four sub-dimensions, the "Student Views on Distance Education" scale was used. The cronbach alpha reliability coefficient of the scale was calculated as 0.864. The research data were collected with the scale form delivered to the students via google forms. In the analysis of normally distributed data, descriptive statistics (frequency, arithmetic mean, standard deviation), independent sample t-test and one-way variance analysis (ANOVA) test were used. "Pearson Correlation Analysis" was conducted to determine the level of relationship among the dependent variables.Results: Statistically significant differences were observed in favor of female students in the sub-dimension of "instructiveness" in the gender variable of the sample group. In addition, significant differences were found among the variables of the department and grade level of the students. As a result of the correlation analysis, it was determined that there was a positive and highly significant relationship between the "Personal Suitability" sub-dimension and the "Effectiveness" sub-dimension (r=0.846;p<0.01).Conclusion: Consequently, the students of the faculty of sports sciences in the study stated that they did not find synchronous distance education practices effective enough compared to those of the traditional education, but that distance education was instructive.
Opinions of Students Who Have Sports Education in the Pandemic (Covid-19) Process on Synchronous Distance Education
Keywords: Sports Medicine; Spor Hekimliği